Pembatasan Masa Jabatan Anggota Legislatif dalam Bingkai Demokrasi Konstitusional - Kevin Mardianto (CV Rewang Rencang, 2025)
This research explores the urgency of term limits for legislative members within the framework of constitutional democracy, aiming to prevent abuse of power, oligarchic dominance, and political stagnation. Using a normative juridical method and qualitative descriptive analysis, the study reveals that the absence of legislative term limits reflects a weakness in Indonesia’s legal system. The findings emphasize the importance of structural term limits as a mechanism for power control, ensuring political regeneration, and strengthening the principles of equality before the law and fair representation in a democratic constitutional state.